STUDI MENGENAI VALUE CO-CREATION DAN PENGARUHNYA TERHADAP CONSUMER BRAND ENGAGEMENT PADA PEMASARAN JASA HENNA DI MEDIA SOSIAL - Nila Masalikul Masruroh (Jurnal Akuntansi dan Pajak, 2023)
This study aims to examine the effect of Value Co-Creation on Consumer Band Engagement on the marketing of henna services on social media which includes Entertainment, Customization, Interactivity, EWOM and Trendiness. Sampling was used using a purposive sampling technique, the total sample used was 150 respondents who were henna service users and active on social media. The data analysis technique used in this research is using SEM (structural equation model) analysis with the AMOS program, and data collection techniques using a questionnaire. The results show that there are five hypotheses that have a positive and significant effect, namely entertainment on value co-creation, interactivity on value co-creation, EWOM on value co-creation, trendiness on value co-creation, and value co-creation on consumer brand engagement, and one hypothesis that is not significant is the customization of value co-creation. Keywords : Entertainment, Customization, Interactivity, Electronic Word of Mouth, Trendiness, Value Co-Creation, Consumer Brand Engagement